2023
DOI: 10.1002/alz.13355
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tau deposition and hypometabolism on cognitive impairment and longitudinal cognitive decline

Abstract: INTRODUCTIONTau and neurodegeneration strongly correlate with cognitive impairment, as compared to amyloid. However, their contribution in explaining cognition and predicting cognitive decline in memory clinics remains unclarified.METHODSWe included 94 participants with Mini‐Mental State Examination (MMSE), tau positron emission tomography (PET), amyloidPET, fluorodeoxyglucose (FDG)PET, and MRI scans from Geneva Memory Center. Linear regression and mediation analyses tested the independent and combined associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…We next examined the coupling-thickness association, as tau is closely associated with cortical atrophy and ultimately leads to cognitive decline ( 12, 54 ). Similar to the coupling-tau links above, gBOLD-CSF coupling was also significantly related to cortical thickness in widespread cortical regions, including the Braak V-VI ROI, Braak III-IV ROI, and temporal meta-ROI, across the entire group of subjects, and more specifically among the impaired Aβ+ subjects ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the coupling-thickness association, as tau is closely associated with cortical atrophy and ultimately leads to cognitive decline ( 12, 54 ). Similar to the coupling-tau links above, gBOLD-CSF coupling was also significantly related to cortical thickness in widespread cortical regions, including the Braak V-VI ROI, Braak III-IV ROI, and temporal meta-ROI, across the entire group of subjects, and more specifically among the impaired Aβ+ subjects ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with results from other studies, demonstrating high regional variance of tau-deposition patterns in AD and symptom-dependent association with tau-deposition in function-related brain regions (Bejanin et al, 2017; Brier et al, 2016; Vogel et al, 2021). First, an association has been shown between the overall severity of cognitive decline (as assessed by the Mini Mental Status Examination/MMSE) and tau burden, as measured in a large cortical meta-ROI as well as in the lateral temporal cortex (Bejanin et al, 2017; Boccalini et al, 2024; Brier et al, 2016). Importantly, pronounced tau-deposition in individual brain regions has been associated not only with overall cognitive impairment but also with specific decline of different cognitive functions associated with the respective brain areas (Dronse et al, 2016; Ossenkoppele et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the detected clusters do not overlap with brain regions where tau deposition has been associated with overall severity of cognitive decline, such as the lateral temporal cortex (Boccalini et al, 2024). Also, the parts of the praxis network involved are not among the brain regions affected by tau pathology early in the disease course (such as entorhinal cortex, Brodman area 35, neocortical temporal cortex (Berron et al, 2021)).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 3 broad categories of biomarkers in both 2018 initial and 2023 updated A/T/N research frameworks by the National Institute on Aging and the Alzheimer’s Association (NIA-AA), the detection of the misfolded proteins including Aβ and tau through the brain molecular imaging and body fluid examination was at the core of the framework [22, 60]. A new study evaluating the importance of various brain imaging modalities in monitoring cognition and predicting cognitive decline in memory clinics has observed that neocortical tau pathology is the main determinant of cognitive decline over time and the prognostic value of tau-PET surpassed all other neuroimaging measures [7]. One of the significant advances in the updated 2023 research framework is the addition of plasma biomarkers developed recently to the new version, while the 2018 version mainly depended on biomarkers from CSF and brain imaging [22, 60].…”
Section: Discussionmentioning
confidence: 99%